Enhancing the therapeutic efficacy of gemcitabine in bladder cancer through TGF-β1 inhibition and pluronic F-127-based microsphere delivery - Yaoyao Xiong; Yangle Li; Lingxiao Chen; Minfeng Chen; Wei He; Lin Qi (Journal of Biological Engineering)
Abstract Bladder cancer is prevalent and features significant recurrence and progression rates, necessitating effective treatment strategies. Gemcitabine, commonly used to treat non-muscle invasive bladder cancer (NMIBC), shows moderate efficacy and notable side effects. TGF-β, not only a key in epithelial-mesenchymal transition(EMT) but also in tumor development, offers a target for enhancing gemcitabine efficacy. The present research was designed to explore the impact of TGF-β1 inhibitors (LY2109761 and LY3200882) with or without gemcitabine on bladder cancer cells and to develop Pluronic F-127-based microspheres (MSs) for drug delivery. TGF-β1 inhibitors significantly reduced cell viability, promoted apoptosis, and inhibited invasion in bladder cancer cell lines 5637 and SW780, with LY3200882 showing superior efficacy. Combining LY3200882 with gemcitabine enhanced these effects, indicating a synergistic interaction. Drug-loaded MSs were prepared, characterized by smooth morphology and consistent size distribution, and demonstrated sustained drug release, sufficient physical integrity, and no significant cytotoxicity to normal human fibroblast cells. In vitro, gemcitabine encapsulated in MSs exhibited enhanced cytotoxicity, apoptosis induction, and invasion inhibition compared to non-encapsulated gemcitabine. In vivo, these MSs significantly reduced tumor weight and volume, with notable reductions in blood vessel and cancer cell density, and altered expression of proliferation and apoptosis markers, particularly in the gemcitabine + LY3200882 MSs group. Systemic and local bladder toxicity assessments in mice demonstrated the in vivo safety of drug-loaded MSs. This study concludes that combining TGF-β1 inhibitors with gemcitabine in Pluronic F-127-based MSs enhances therapeutic efficacy against bladder cancer, promoting apoptosis, inhibiting cell invasion, and reducing tumor growth and metastasis while maintaining safety. Graphical Abstract